2020
DOI: 10.1038/s41598-020-79357-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical characterization of the main protease, 3-chymotrypsin-like protease (3CLpro) from the novel coronavirus SARS-CoV 2

Abstract: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) is responsible for the novel coronavirus disease 2019 (COVID-19). An appealing antiviral drug target is the coronavirus 3C-like protease (3CLpro) that is responsible for the processing of the viral polyproteins and liberation of functional proteins essential for the maturation and infectivity of the virus. In this study, multiple thermal analytical techniques have been implemented to acquire the thermodynamic parameters of 3CLpro at different buffer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
3
36
1
1
Order By: Relevance
“…The expression and purification of recombinant 3CLpro was described previously ( Ferreira and Rabeh, 2020 ). Briefly, the expression of pET28b(+) vector containing 3CLpro in Escherichia coli BL21-CodonPlus-RIL (Stratagene) was initiated by the addition of 10 ml of an overnight starting culture in LB broth to 1 L of terrific broth supplemented with kanamycin and chloramphenicol (50 μg/ml final concentration of both).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression and purification of recombinant 3CLpro was described previously ( Ferreira and Rabeh, 2020 ). Briefly, the expression of pET28b(+) vector containing 3CLpro in Escherichia coli BL21-CodonPlus-RIL (Stratagene) was initiated by the addition of 10 ml of an overnight starting culture in LB broth to 1 L of terrific broth supplemented with kanamycin and chloramphenicol (50 μg/ml final concentration of both).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal unfolding signal of proteins was assessed from the increase of the fluorescence intensity of 5× concentrated SYPRO Orange dye, with the excitation and emission wavelengths of 492 and 610 nm, respectively. The thermal unfolding data were then fitted to Boltzmann sigmoidal function to calculate the melting temperature ( T m ) value of the different 3CLpro variants in the midpoint of the thermal transition using the Excel add-on package XLft (IDBS limited, Bridgewater, NJ, United States), as described previously ( Ferreira and Rabeh, 2020 ). In addition, the T m of the WT and mutants of the 3CLpro was determined at different enzyme concentrations from 25 to 200 μM to evaluate the thermal stability for the monomeric and dimeric states of the protease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The far-UV CD spectrum of the ectodomain G protein at physiological pH 7.5 suggested that the structure of the protein is a mixture of β-sheet and α-helix with two ellipticity minima at 208 and 222 nm. 23 We recorded the far-UV CD spectra at 25 and 85 °C and then again at 25 °C after cooling to check the reversible nature of the protein. We also observed the behavior of the protein’s secondary structure content at different pH values.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of our protein at different pH values were similar to that of a chymotrypsin-like fold that has a mixture of β-sheet and α-helical structures and exhibits two ellipticity minima at 222 nm and 208. 23 The ectodomain G protein spectrum at pH 7.5 was initially measured at 25 °C. The protein was then heated up to 85 °C, and the spectrum was recorded.…”
Section: Discussionmentioning
confidence: 99%